An Investigation into Teachers' views on Effective Teaching Strategies for Nutrition Education in a DEIS band 1 context. - Kelly, Niamh (My University, 2019)
The prevalence of childhood obesity has increased significantly worldwide over the past three decades, with over one in four Irish children identified as being overweight or obese at present. There is a known higher prevalence of childhood obesity in areas of economic disadvantage. Nutrition Education (NE) from an early age can equip the child with the appropriate knowledge needed for them to make wellinformed decisions relating to food and nutrition. Teachers have a significant role to play in the provision of NE, especially in low income areas where children may not receive this at home. The aim of this research was to investigate teachers‚Äô views on effective teaching strategies for nutrition education in a DEIS band 1 context. The research design used was a qualitative method. The researcher completed a total of nine interviews with an array of teachers from different class levels in a DEIS band 1 school. The present study found that almost one half of the teachers were unaware of the recent statistics indicating the prevalence of childhood obesity in Ireland, however identified obesity as a problem in their school. Teachers identified child-centred, active methodologies as effective strategies for NE implementation, across all class levels. This research discovered that the main barriers to effective NE implementation were lack of time, lack of concrete resources and lack of parental involvement when it comes to implementing NE in practice. Further research similar to this study should be conducted on a larger scale in order to pinpoint exactly how best to implement nutrition education in the current climate of growing childhood obesity prevalence.
Professional Master of Education
Keywords: Research Subject Categories; Childhood obesity; Economic disadvantage; Nutrition Education; Parental involvement